Spaces of inclusion: investigating place, positioning and perspective in educational settings through photo-elicitation. Issue 1 (2nd January 2018) - Dunne, Linda; Hallett, Fiona; Kay, Virginia; Woolhouse, Clare
ABSTRACT: This paper presents findings from a collaborative research study which sought to explore perspectives and understandings of the concept of inclusion, as played out in schools and colleges in northwest England, via the use of images. The research had two parts: in the first part, children and young people took photographs in their school setting that they felt represented inclusion or exclusion, offering an explanation for their choice. Some of these photographs and the accompanying comments were anonymised and formed the second part of the research that sought the viewpoints and perspectives of student-teachers, serving teachers, teaching assistants and academics via seminars and workshops. It is the responses received in the seminars and workshops that form the focus of this paper. Four images and a range of responses to them have been selected for discussion and are framed within three key inter-related themes of place, positioning and perspective. Such an analysis is made to consider how self-positioning might inform diverse interpretations of the cultural construction and visual representation of inclusion and exclusion.